The Efficacy of Cognitive-Behavioral Therapy on Coping Strategies and Anxiety Sensitivity of Patients With COVID-19 Obsession - Farzin Bagheri Sheykhangafshe; Ali Fathi-Ashtiani; Vahid Savabi Niri; Samaneh Otadi; Hamed Rezaei Golezani (Gonabad University of Medical Sciences, 2023)
Background: One of the factors affecting people's mental health is having repeated and confused thoughts about COVID-19. In this regard, the present study was conducted to investigate the effectiveness of cognitive-behavioral therapy on coping strategies and anxiety sensitivity of patients with COVID-19 obsession. Methods: The present research method was quasi-experimental and pre-test-post-test design with a control group. The statistical population of the study included patients with COVID-19 obsession in 2021. The study sample includes 30 patients with COVID-19 obsession who were selected using the convenience sampling method and were randomly divided into two experimental groups (n=15) and control groups (n=15). The collection tool included a questionnaire on COVID-19 obsession, coping strategies, and anxiety sensitivity. The experimental group received ten 90-minute sessions of cognitive-behavioral therapy, but the control group received no intervention. Finally, the obtained data were analyzed by multivariate covariance analysis in SPSS software, version 24 (P<0.05). Results: The results showed that cognitive-behavioral therapy significantly increased the problem-oriented coping strategy and decreased the emotion-oriented coping strategy, avoidance coping strategy, and anxiety sensitivity (physical, cognitive and social) in patients with COVID-19 obsession (P<0.01). Conclusion: The obtained findings indicated that cognitive-behavioral therapy can significantly improve the patients with COVID-19 obsession. Considering the long-term consequences of COVID-19, psychology and counseling centers should take measures to identify and treat vulnerable groups.